2023
DOI: 10.3390/toxics11030242
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Toxicity and Antioxidant Mechanism of Photoaging Microplastics on Pisum sativum L. Seedlings

Abstract: Recent studies have confirmed that changes in the physical properties of microplastics (MPs) trigger toxicological effects and ecological risks. To explore the toxicity of different types of MPs on plants, and the influence of MP photoaging, this study investigated the toxicity mechanisms of pristine, 7 and 14 d photoaged polystyrene (PS), polyamide (PA), polyethylene (PE), and polyethylene terephthalate (PET) MPs on seed germination, root growth, nutrient fraction, oxidative stress, and antioxidant systems of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…The increasing trend in the enzyme activity was similar to the increasing concentration of TBBPA in the binary system, which revealed that the toxicity of TBBPA was relatively obvious at concentrations between 0.5 and 8 mg L −1 . As an initial protection line against ROS accumulation and membrane lipid peroxidation, SOD primarily converts the acutely toxic ˙O 2 − to less toxic H 2 O 2 , 43 as evidenced by the levels of ˙O 2 − and H 2 O 2 in the algal cells. Previous studies have confirmed that an increase in SOD activity is associated with the activation of repair functions and is a sign of elevated antioxidant status, 44 implying that the activation of the antioxidant system enhanced the plant tolerance and resistance to binary ZnO NPs.…”
Section: Resultsmentioning
confidence: 99%
“…The increasing trend in the enzyme activity was similar to the increasing concentration of TBBPA in the binary system, which revealed that the toxicity of TBBPA was relatively obvious at concentrations between 0.5 and 8 mg L −1 . As an initial protection line against ROS accumulation and membrane lipid peroxidation, SOD primarily converts the acutely toxic ˙O 2 − to less toxic H 2 O 2 , 43 as evidenced by the levels of ˙O 2 − and H 2 O 2 in the algal cells. Previous studies have confirmed that an increase in SOD activity is associated with the activation of repair functions and is a sign of elevated antioxidant status, 44 implying that the activation of the antioxidant system enhanced the plant tolerance and resistance to binary ZnO NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Due to large amount of pesticides handled, close contact with pesticides or the treated crops, agricultural workers have a greater risk of being exposed to pesticides and associated health effects than the general public [1]. Despite the inherent toxicity of pesticides, nurseries often rely on the heavy use of pesticides for high-quality flowers, fruits and vegetables, leading to various health risks towards non-target organisms [2].…”
Section: Introductionmentioning
confidence: 99%